Protection of Medical Personnel and Health Care Facilities: A Few Guiding Principles of Islamic Law - Ahmad, Muhammad Mushtaq (Journal of Islamic and Religious Studies, 2017)
Muslims scholars in principle agree that non-combatants are protected and that they lose protection when they directly participate in hostilities. However, the issues of defining the scope of non-combatant and that of direct participation remain contentious which resultantly cause confusions about the protection of medical personnel. The present paper digs out principles of Islamic law relating to the protection of medical personnel during armed conflict and for this purpose focuses on a doctor who works for humanity and who provides medical assistance to all and gives priority on the basis of need only. It tries to find answers to questions such as: is the doctor muqatil (combatant)? Does the act of providing medical assistance to the enemy combatants make the doctor liable for direct participation in hostilities? Does Islamic law distinguish between the legal consequences of direct and indirect participation in hostilities? After exploring the rich Islamic legal literature on the protection of medical personnel during armed conflict, the paper also examines the legal consequences of abuse of the protected status.